2012
DOI: 10.5562/cca2123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization and Hydrogen Bonding of Mono(salicylidene)carbohydrazide

Abstract: Abstract. The condensation reaction between carbohydrazide and salicylaldehyde in different solvents gave mono(salicylidene)carbohydrazide (1). The structure of 1 in solution has been determined by using experimental (NMR and UV spectroscopies and Mass spectrometry) and quantum chemical (DFT) methods. It has been demonstrated that 1 adopts the hydroxy-one tautomeric form which is in accordance with previously published results for the related systems. Changes in NMR chemical shifts and calculations have pointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The recorded titration curves were almost exactly superimposed, therefore the protonation constants calculated from the two consecutive titrations were found to be equal within ±0.05 log units, which indicated that no decomposition occurred. According to the literature, the neutral and completely protonated STSC (H 2 L ) ligand is present in the hydroxy (OH)–thione (NHC=S) form in the solid state,16 and the similar tautomeric form of a methoxy derivative of STSC was found in solution 17. Thus, two proton‐dissociation processes of STSC could be determined by pH potentiometry and UV/Vis spectrophotometry.…”
Section: Resultssupporting
confidence: 84%
“…The recorded titration curves were almost exactly superimposed, therefore the protonation constants calculated from the two consecutive titrations were found to be equal within ±0.05 log units, which indicated that no decomposition occurred. According to the literature, the neutral and completely protonated STSC (H 2 L ) ligand is present in the hydroxy (OH)–thione (NHC=S) form in the solid state,16 and the similar tautomeric form of a methoxy derivative of STSC was found in solution 17. Thus, two proton‐dissociation processes of STSC could be determined by pH potentiometry and UV/Vis spectrophotometry.…”
Section: Resultssupporting
confidence: 84%
“…Other authors have applied the PCM model successful to predict the conduct of a tautomeric equilibrium in solution 26–30…”
Section: Resultsmentioning
confidence: 99%
“…After the addition of salicylaldehyde (0.71 mL, 6.67 mmol) and a few drops of piperidine, the reaction mixture was heated at 55 °C and stirred under reflux for 40 min [9]. During heating, a white crystalline product started to precipitate.…”
Section: Synthesismentioning
confidence: 99%
“…These compounds can easily be prepared by the condensation reaction between carbohydrazide and appropriate aldehyde or ketone. The condensation of carbohydrazide (I) with salicylaldehyde (II) yielded a mixture of mono-(III) and bis(salicylidene)carbohydrazide (IV), as shown in Figure 1 [9,10]. We have recently reported that in-line Raman spectroscopy combined with multivariate data analysis could be applied for in-line monitoring of condensation reaction and for assessing the mixture content [11].…”
Section: Introductionmentioning
confidence: 99%